Invisible Play and Invisible Game: Video Game Testers or The Unsung Heroes of Knowledge Working - Marco Briziarelli (tripleC: Communication, Capitalism & Critique)
In this paper, I examine video game testing as a lens through which exploring broader aspects of digital economy such as the intersection of different kind productive practices—working, labouring, playing and gaming—as well as the tendency to conceal the labour associated with them. Drawing on Lund’s (2014) distinction between the creative aspects of “work-playing” and the constraining/instrumental aspects of “game-labouring”, I claim that video game testing is buried under several layers of invisibility. Ideologically, the “playful”, “carnivalesque”, quasi-subversive facets of this job are rejected because of their resistance to be easily subsumed by the logic of capitalism. Practically, a fetishist process of hiding human relations behind relations among things (elements in the video game environment) reaches its paradoxical apex in the quality assurance task of this profession: the more the game tester succeeds in debugging games higher is the fetishization of his/her activity.